2013
DOI: 10.14735/amko2013263
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Banding Analysis of Peripheral Blood Lymphocytes Stimulated with IL-2 and CpG Oligonucleotide DSP30 in Patients with Chronic Lymphocytic Leukemia

Abstract: hematologická a onkologická klinika, Centrum molekulární bio logie a genové terapie, LF MU a FN Brno 2 Oddělení lékařské genetiky, laboratoř molekulární cytogenetiky, LF MU a FN Brno 3 CEITEC-Středoevropský technologický institut, MU, Brno Souhrn Východiska: Chromozomové změny patří u chronické lymfocytární leukemie (CLL) mezi významné prognostické faktory. Hlavní metodou využívanou k detekci těchto chromozomových změn je fl uorescenční in situ hybridizace (FISH), klasické cytogenetické vyšetření vyžadující bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In PB B-cells, abnormalities ranked to a poor prognosis group by karyotyping results were reported in 6 cases (No. 1,2,10,11,13,14). The group attri buted to the favorable cytogenetical prognosis included 6 cases (No.…”
Section: Results Ans Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PB B-cells, abnormalities ranked to a poor prognosis group by karyotyping results were reported in 6 cases (No. 1,2,10,11,13,14). The group attri buted to the favorable cytogenetical prognosis included 6 cases (No.…”
Section: Results Ans Discussionmentioning
confidence: 99%
“…To improve the effectiveness of cytogenetic studies, the attempts were made to use other stimulators of the cell cycle. Among the new mitogens, the CpGoligodeoxynucleotide DSP30 (CpG-ODN) [10] is used. Thus, detection of chromosomal abnormalities increases to 80% of cases.…”
mentioning
confidence: 99%
“…showed a consistent and reproducible increase in detection rate of abnormal clones using CpG‐ODN as compared with traditional mitogens (pokeweek mitogen and TPA). Multiple other studies have shown an increase in detection rate of CLL to around 80% with CpG‐ODN The addition of the cytokine IL‐2 has also been shown to reduce apoptosis in replicating B cells and improve detection rate .…”
Section: Introductionmentioning
confidence: 99%